2016
DOI: 10.1074/jbc.m115.678029
|View full text |Cite
|
Sign up to set email alerts
|

Wilms Tumor Suppressor, WT1, Cooperates with MicroRNA-26a and MicroRNA-101 to Suppress Translation of the Polycomb Protein, EZH2, in Mesenchymal Stem Cells

Abstract: Hereditary forms of Wilms arise from developmentally arrested clones of renal progenitor cells with biallelic mutations of WT1; recently, it has been found that Wilms tumors may also be associated with biallelic mutations in DICER1 or DROSHA, crucial for miRNA biogenesis. We have previously shown that a critical role for WT1 during normal nephrogenesis is to suppress transcription of the Polycomb group protein, EZH2, thereby de-repressing genes in the differentiation cascade. Here we show that WT1 also suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…3B). It has been previously shown that WT1 interacts with the microRNA pathway components DICER and AGO2 (Akpa et al, 2016). WT1 interaction with AGO1 and AGO2 was confirmed in the mesonephric cells ( Fig.…”
Section: Wt1 Interacts With the Microrna Pathway Componentssupporting
confidence: 59%
“…3B). It has been previously shown that WT1 interacts with the microRNA pathway components DICER and AGO2 (Akpa et al, 2016). WT1 interaction with AGO1 and AGO2 was confirmed in the mesonephric cells ( Fig.…”
Section: Wt1 Interacts With the Microrna Pathway Componentssupporting
confidence: 59%
“…Mutations in WT1 gene have been implicated in abnormal development of the genito-urinary system resulting in syndromes such as Wilm's Tumor, Denys-Drash, WAGR and Frasier [4][5][6][7][8]. Recent studies however suggest an even wider spectrum of functions for WT1, including epigenetic regulation of genes [9][10][11][12], stem cell differentiation [13] and genome stability [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these data suggested that miR-30a-5p could be a potential therapeutic target of CCA. miR-30a-5p, as a member of the mir-30 family, plays a crucial role in tumor growth and metastasis [5,6]. Currently, the expression profile and function of miR-30a-5p in different malignancies are still existed controversies.…”
Section: Discussionmentioning
confidence: 99%
“…More evidence showed that the dysfunction or abnormal expression of miRNAs maybe lead to incidence of human malignancies, and play important roles in tumor growth and metastasis [5,6]. Furthermore, miRNAs can as the biomarker of the diagnosis and as potential cancer therapeutics [7,8].…”
Section: Ivyspring International Publishermentioning
confidence: 99%